Identification and characterization of a novel chromosomal aminoglycoside 3’-O-phosphotransferase, APH(3′)-Id, from Kluyvera intermedia DW18 isolated from the sewage of an animal farm - Sha, Yuning; Lin, Naru; Zhang, Guozhi; Zhang, Yuan; Zhao, Jingxuan; Lu, Junwan; Zhu, Tingting; Zhang, Xueya; Li, Qiaoling; Zhang, Hailin; Lin, Xi; Li, Kewei; et al. (Frontiers in Microbiology, 2023)
Background: Aminoglycosides, as important clinical antimicrobials, are used as second-line drugs for treating multidrug-resistant tuberculosis or combined with β-lactam drugs for treating severe infections such as sepsis. Aminoglycoside-modifying enzyme (AME) is the most important mechanism of aminoglycoside resistance and deserves more attention. Methods: The bacterium Kluyvera intermedia DW18 was isolated from the sewage of an animal farm using the conventional method. The agar dilution method was used to determine the minimum inhibitory concentrations (MICs) of antimicrobials. A novel resistance gene was cloned, and the enzyme was expressed. The kinetic parameters were measured by a SpectraMax M5 multifunctional microplate reader. Bioinformatic analysis was performed to reveal the genetic context of the aph(3’)-Id gene and its phylogenetic relationship with other AMEs. Results: A novel aminoglycoside 3′-O-phosphotransferase gene designated aph(3’)-Id was identified in K. intermedia DW18 and shared the highest amino acid identity of 77.49% with the functionally characterized aminoglycoside 3′-O-phosphotransferase APH(3’)-Ia. The recombinant plasmid carrying the novel resistance gene (pMD19-aph(3’)-Id/E. coli DH5α) showed 1024-, 512-, 128- and 16-fold increased MIC levels for kanamycin, ribostamycin, paromomycin and neomycin, respectively, compared with the reference strain DH5α. APH(3’)-Id showed the highest catalytic efficiencies for ribostamycin [kcat/Km of (4.96 ± 1.63) × 105 M-1/s-1], paromomycin [kcat/Km of (2.18 ± 0.21) × 105 M-1/s-1], neomycin [kcat/Km of (1.73 ± 0.20) × 105 M-1/s-1], and kanamycin [kcat/Km of (1.10 ± 0.18) × 105 M-1/s-1]. Three conserved functional domains of the aminoglycoside phosphotransferase family and six amino acid residues responsible for the phosphorylation of kanamycin were found in the amino acid sequence of APH(3’)-Id. No mobile genetic element (MGE) was discovered surrounding the aph(3’)-Id gene. Conclusion: In this work, a novel aminoglycoside 3’-O-phosphotransferase gene designated aph(3’)-Id encoded in the chromosome of the environmental isolate Kluyvera intermedia DW18 was identified and characterized. These findings will help clinicians select effective antimicrobials to treat infections caused by pathogens with this kind of resistance gene.